Mitos Nasi Punar Pengantin Ditinjau Dalam Perspektif Urf: The Myth of the Nasi Punar Bride Reviewed in the Perspective of Islamic Law - Aprilianti, Fani; Anisah, Inayatul (Institut Agama Islam Negeri Fattahul Muluk Papua, 2023)
In the current era of globalization and easy access to information technology, people's beliefs that have developed and existed since time immemorial have not diminished, such as the myth of Nasi Punar Bride, this myth has developed and is still believed by the people in Gelang Village, Sumberbaru District, Jember Regency, this belief includes that This punar rice can improve the fortunes of brides and grooms, can quickly find a soul mate for those who are still single, can cause household harmony as well as cause separation. Starting from the facts that occur in society, the author is interested in researching the myth of the nasi punar bridal reviewed from the perspective of Islamic law. The aims of this research are as follows: firstly, to find out the law for people who believe in the myth of nasi punar bridal viewed from the perspective of urf, secondly, what are the legal consequences if they believe it? the myth of bridal rice punar from a urf perspective. This research is a type of empirical research / field research using the urf approach method. Data collection techniques were carried out by means of interviews, observation and documentation. Data analysis goes through the stages of data collection, data reduction, data presentation and drawing conclusions. In order to test the validity of the data, the author used a triangulation technique, so that the results of this research concluded that: the practice of nasi punar in Gelang village, Sumberbaru sub-district, Jember district is carried out by the entire community with the aim of respecting the cultural heritage of ancestors, the ingredients and procession do not violate the rules of Islamic law, Regarding the myths circulating about this tradition, it is only believed by some parents whose thinking is still old-fashioned. In terms of urf, this tradition is included in the category of urf authentic / good tradition because there is no harm found in it. This tradition is also carried out outside of marriage, and does not in any way harm the validity of the marriage contract, so this tradition is permissible or permissible to carry out and preserve.